Utilization of sugar cane by-product and biological agents to improve the quality of rice - Oktavia Sarhesti Padmini; Sri Wuryani; Rukmowati Brotodjojo (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2014)
The purpose of this study was to examine the effect of boiler ash which is a waste of sugar industry and liquid organic fertilizer (LOF) to improve the quality of rice. Experiments were set up using split plot and arranged in completely randomized design, with three replicates. Main plots were composed of inorganic fertilizers on 2 levels, namely: 100% farmer’s dose and 50% farmer’s dose plus boiler ash 10 tons/ha. Sub plots was spraying frequency of LOF